The influence of Y2O3 concentration on the microstructure and oxidation performance of FeCrAl-ODS alloy manufactured by selective laser melting - Zhang, Shenghua; Li, Fudong; Xie, Yu; Li, Zhonghua; Wang, Yu; He, Shengtong; Liu, Bin (Journal of alloys and compounds, 2025)
This study investigates the influence of Y₂O₃ concentration on the microstructure and oxidation performance of selective laser melted (SLM-ed) FeCrAl-ODS alloys. Three FeCrAl-ODS alloys with varying Y₂O₃ contents were designed, and their microstructures were characterized. Oxidation experiments were conducted at 1000 °C in air. The results indicate that FeCrAl0.7Y exhibited fine grain size and high interior strain due to the nucleation-promoting and grain boundary-pinning effects of Y₂O₃ particles. After 225 h of oxidation, FeCrAl0.1Y demonstrated the lowest oxidation mass gain and excellent oxide scale adhesion. Dense and compact Al₂O₃ scales formed on the surfaces of SLM-ed FeCrAl alloys with Y₂O₃ additions. Y enrichment at the Al₂O₃ oxide grain boundaries inhibited outward cation diffusion, shifting the Al₂O₃ scale growth mechanism from a bidirectional mechanism driven by metallic element diffusion and inward oxygen diffusion to a columnar grain growth mechanism dominated by inward oxygen diffusion. This change impeded the growth rate of oxide scale. However, excessive Y accelerated oxide film development. The presence of Y improved the adhesion of the oxide film on the SLM-ed FeCrAl-ODS alloys. ●The effect of Y2O3 content on the microstructure and oxidation behavior of FeCrAl-ODS alloy fabricated by SLM was studied.●The nucleation-promoting and boundary-pinning effects of Y₂O₃ particles lead to fine grains and high interior strain.●The influence of Y on the Al₂O₃ scale growth mechanism is independent of the fabrication method.●The segregation of Y alters the bidirectional growth mechanism of the Al₂O₃ layer into a predominantly inward diffusion.●The segregation of Y reduced the oxide scale growth rate, whereas an excessive amount of Y accelerated oxide layer growth.